SEISMIC DESIGN FOR INFRASTRUCTURES - I Wayan Redana; I Made Aryatirta Predana; I Kadek Edy Suhendrawan; I Ketutu Sudarsana (Jurnal Ilmiah Teknik Sipil, 2024)
Seismic design for infrastructures such as building and non-building is designed based on design ground shaking shall be characterized by the design spectrum. This study aims to evaluate seismic design for infrastructures following SNI 1726-2019. Several site investigations are taken by conducting boring to a depth of 30 m to count the soil site classification. It might be summarized that the area of investigation is classified as SC/hard soil, very solid and soft rock, SD/medium soil and SE (soft soil).